2020
DOI: 10.1111/acps.13235
|View full text |Cite
|
Sign up to set email alerts
|

In search of a dose–response relationship in SSRIs—a systematic review, meta‐analysis, and network meta‐analysis

Abstract: Objective Recent meta‐analyses on dose–response relationships of SSRIs are largely based on indirect evidence. We analyzed RCTs directly comparing different SSRI doses. Method Systematic literature search for RCTs. Two raters independently screened articles and extracted data. Across SSRIs, doses defined as low, medium, and high doses, based on drug manufacturers’ product monographs, were analyzed in pairwise random‐effects meta‐analyses and in a sensitivity network meta‐analysis with regard to differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Pharmacological treatments exist, but a number of articles have emphasized the inability of antidepressant medication to consistently demonstrate superiority to placebo, in patients with mild or moderate symptoms (3). Side effects of such treatments, including nausea and drowsiness, are also common, especially at medium to high doses in the case of selective serotonin reuptake inhibitors (SSRIs) (4). Alternative treatments, such as natural products or exercise for combating mood disorders, are therefore being explored (5).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatments exist, but a number of articles have emphasized the inability of antidepressant medication to consistently demonstrate superiority to placebo, in patients with mild or moderate symptoms (3). Side effects of such treatments, including nausea and drowsiness, are also common, especially at medium to high doses in the case of selective serotonin reuptake inhibitors (SSRIs) (4). Alternative treatments, such as natural products or exercise for combating mood disorders, are therefore being explored (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although Braun et al 1 showed no significant difference between high and medium doses, if my hypothesis is the case, it seems probable that a further increase in SSRI dose may decrease the effects of SSRIs. In any case, my hypothesis may at least account for the lack of a particularly linear dose–response relationship.…”
Section: Scenementioning
confidence: 65%
“…Braun et al 1 have rigorously performed meta‐analyses on the dose–response relationships of selective serotonin reuptake inhibitors (SSRIs) using all direct comparisons of different dosages of specific SSRIs. They reconfirmed that there were no clinically significant differences among SSRI doses at the low, medium, and high dose category levels, which is consistent with the results of the meta‐analyses performed by Furukawa et al 2 using indirect comparisons and those reported by Dold et al 3 showing nonefficacy of dose escalation after initial nonresponse to standard‐dose pharmacotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a relationship should show in trials randomizing patients to different doses. When scientists did just that, results turned out to be mostly negative: In meta‐analyses we were unable to detect clinically meaningful or statistically significant dose–effect gradients at the level of substance groups—be it SSRIs 3 or SNRIs (manuscript in submitted)—or consistent and positive evidence for specific substances. For example, 225 mg venlafaxine was not statistically significantly inferior to 375 mg, when we summarized three homogeneous studies (SMD: 0.1 [−0.15; 0.37]), neither was 75 mg venlafaxine relative to 150 mg.…”
Section: Dose Increasementioning
confidence: 99%